Tanggung Jawab Notaris Dalam Pembuatan Akta Otentik Dengan Bahasa Asing - Santosa Putra, Arya Bagus Khrisna Budi; Priyanto, I Made Dedy (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p08, 2020)
In Law on the Occupation of Notary Article 43, there are 2 (two) contradicting Paragraphs, namely Paragraph (1) and Paragraph (3). In Paragraph (1) it is stated that "deeds must be made in Indonesian", while in Paragraph (3) it states "if the parties wish, the deed can be drawn up in a foreign language". The disharmony of the 2 (two) rules could potentially reduce the perfection of the deed. As for the problems raised in this study regarding what is the notary's responsibility in making authentic deeds in foreign languages? and what is the urgency of using Indonesian in making authentic deeds? Then the objective of this research is to knowing the Notary's responsibility in making authentic deeds in foreign languages ??and to find out how much urgency the use of Indonesian is in making authentic deeds. This study is using a normative research method with statutory approach. Through this research it is known that the responsibility of notaries in making authentic deeds in foreign languages ??can be classified into administrative, civil and criminal responsibilities, then it is known that the urgency of using Indonesian in making deeds is very important because the regulation of the applicatian of Indonesian in the territory of the Indonesian state is clearly stated in Article 36 of the 1945 Constitution of the Republic of Indonesia.